2017
DOI: 10.1167/17.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Global processing of random-phase radial frequency patterns but not modulated lines

Abstract: Previously, researchers have used circular contours with sinusoidal deformations of the radius (radial frequency [RF] patterns) to investigate the underlying processing involved in simple shape perception. On finding that the rapid improvement in sensitivity to deformation as more cycles of modulation were added was greater than expected from probability summation across sets of local independent detectors, they concluded that global integration of contour information was occurring. More recently, this conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 20 publications
5
36
1
Order By: Relevance
“…Or et al (2011) did compare thresholds for a constant retinal speed and constant angular velocity presentation of their stimulus; however, they only examined these effects on complete motion RFs (i.e., patterns with all cycles of modulation present) and correctly concluded that there was no significant difference in thresholds for these patterns. Our investigation of these effects extended to incompletely modulated motion RF patterns and suggests a result similar to that of Green et al (2017), an interaction between a salient local cue and the global cue of the pattern. The salient local cue is detected first when the global signal is low, but as more cycles of modulation are added, the global signal increases and detection becomes a result of this global cue.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Or et al (2011) did compare thresholds for a constant retinal speed and constant angular velocity presentation of their stimulus; however, they only examined these effects on complete motion RFs (i.e., patterns with all cycles of modulation present) and correctly concluded that there was no significant difference in thresholds for these patterns. Our investigation of these effects extended to incompletely modulated motion RF patterns and suggests a result similar to that of Green et al (2017), an interaction between a salient local cue and the global cue of the pattern. The salient local cue is detected first when the global signal is low, but as more cycles of modulation are added, the global signal increases and detection becomes a result of this global cue.…”
Section: Discussionsupporting
confidence: 57%
“…Both the pattern of results and the comparison to probability summation estimates suggest that motion RF patterns are processed differently to motion line patterns. These findings support that of Green et al (2017), but are contrary to those of (Schmidtmann & Kingdom, 2017) and are discussed as follows.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…More importantly, the method used here generates a combination of many RF patterns, whereas most previous studies used either single component RF patterns (e.g. Bell & Badcock, 2008Bell et al, 2007;Green, Dickinson, & Badcock, 2017, 2018a, Green, Dickinson, & Badcock, 2018bHess, Achtman, & Wang, 2001;Jeffrey et al, 2002;Schmidtmann et al, 2012;Loffler et al, 2003), combinations of two Bell et al, 2007;Lawrence et al, 2016) or three RF components (Schmidtmann, Jennings, & Kingdom, 2015). Given that the aim of this study was to explore the limits of what can be represented by compound RF patterns, the stimuli used here are combinations of an arbitrary number of RF patterns (see Methods).…”
Section: Discussionmentioning
confidence: 99%